Identification and characterization of a novel CASR mutation causing familial hypocalciuric hypercalcemia - Lin, Chien-Ming; Ding, Yi-Xuan; Huang, Shih-Ming; Chen, Ying-Chuan; Lee, Hwei-Jen; Sung, Chih-Chien; Lin, Shih-Hua (Frontiers in Endocrinology, 2024)
Context Although a monoallelic mutation in the calcium-sensing receptor (CASR) gene causes familial hypocalciuric hypercalcemia (FHH), the functional characterization of the identified CASR mutation linked to the clinical response to calcimimetics therapy is still limited. Objective A 45-year-old male presenting with moderate hypercalcemia, hypocalciuria, and inappropriately high parathyroid hormone (PTH) had a good response to cinacalcet (total serum calcium (Ca2+) from 12.5 to 10.1 mg/dl). We identified the genetic mutation and characterized the functional and pathophysiological mechanisms, and then linked the mutation to calcimimetics treatment in vitro. Design Sanger sequencing of the CASR, GNA11, and AP2S1 genes was performed in his family. The simulation model was used to predict the function of the identified mutant. In vitro studies, including immunoblotting, immunofluorescence, a cycloheximide chase study, Calbryte™ 520 Ca2+ detection, and half-maximal effective concentration (EC50), were examined. Results This proband was found to carry a de novo heterozygous missense I554N in the cysteine-rich domain of CASR, which was pathogenic based on the different software prediction models and ACGME criteria. The simulation model showed that CASR I554N mutation decreased its binding energy with Ca2+. Human CASR I554N mutation attenuated the stability of CASR protein, reduced the expression of p-ERK 1/2, and blunted the intracellular Ca2+ response to gradient extracellular Ca2+ (eCa2+) concentration. The EC50 study also demonstrated the correctable effect of calcimimetics on the function of the CASR I554N mutation. Conclusion This novel CASR I554N mutation causing FHH attenuates CASR stability, its binding affinity with Ca2+, and the response to eCa2+ corrected by therapeutic calcimimetics.